Limitation of Foreign Investment in the Banking Sector in Indonesia - Addinul Haq Yaqub; Adi Kadir; Muhammad Naufal Ali Syafi'i (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The liberalization of the banking sector as an implication of Act No. 10 of 1998 regarding amendment of Act No. 7 of 1992 concerning Banking comes into force. In a state, banking has become one of the most crucial sectors in economic matters. Its role is to stimulate the economic growth in the state, according to Mohammad Hatta, the bank is the principle of improvement in the society if a bank does not exist then there will be no improvement like nowadays. Purpose/Objective study: The research aims to describe and examines issues of the Effect of Foreign Capital Restrictions in the Indonesian Banking Sector in a legal, economic, and political perspective. The study looked from the Conception of Welfare State and the Political Strategy of the Law of Economic Development In the case of Foreign Capital Restrictions in the Indonesian Banking Sector to compete globally.Methodology/Approach: This legal writing is normative juridical research that uses a statute approach and a historical approach to be able to provide solutions to existing legal issues.Findings: The results of the analysis show that the Politics of the law of foreign investment in the banking sector must be referred to Banking Act of 1992 in Article 22-26 before anything happens that endangers the interests of the nation and the State. Also, it needs for regulations from Bank Indonesia to leverage foreign capital in the banking sector that will directly improve the economy in the real sector, in order to anticipate the impact of foreign capital ownership in the future of Indonesian banks.